A doença falciforme e suas manifestações bucais - Pedro, Karla Panice (2013)
The Sickle-cell disease is the most prevalent genetic hemoglobinopathy in the Brazilian population, being most frequent in the southeast and northeast regions. The hemonoglobin present in this pathology is the HbS, resulting from the mutation which substitutes the glutamic acid for valine in the sixth position of the beta-globin chain. The beta-globin gene haplotypes are named according to the geographic region and the ethnic group in which they are frequently found, for instance, Central African Republic (CAR), Benin (BEN), Cameroon (CAM), Hindu-Arabic (ARB) and Senegal (SEN). The present study aims to know the characteristics of the disease in the patients of the Mid East Region of the state of São Paulo, identify its oral manifestations in order to diagnose their needs and plan the actions for oral attendance. 41 patients from Bauru, Araçatuba, Jaú and Marília, of both genders, from 1 to 22 years old, have been examined. The oral examination has been performed with artificial light, by a unique examiner and an annotator. The oral conditions have been registered using the ceo-d and the CPO-D indexes. Color, shape, number and occlusion, lips, oral mucosa, tongue, palate, frenulum of lips and lingual frenulum have been examined. The indexes pointed to the need of preventive dental care, dental restoration, surgical and orthodontic treatment. The main signs noticed in the patients have been: pale mucosa in 51%; bad occlusion in 51%; and alteration of color of the teeth in 29, 3%. The study has come to a conclusion that due to the characteristics of these patients, there is a necessity for a multidisciplinary team to attend these patients assuring and promoting their health, avoiding the aggravation of their systemic medical condition.